Implementasi Fuzzy Mamdani untuk Klasifikasi Kualitas Laptop Berdasarkan Parameter Spesifikasi - Bambang Cahyono; Agusdi Syafrizal; Subhan Hartanto (JSAI (Journal Scientific and Applied Informatics), 2025)
This study implements the Mamdani fuzzy logic method to classify laptop quality based on key technical specifications, including processor performance, RAM capacity, storage type, and price. The fuzzy model was developed using linguistic membership functions and rule-based inference to represent expert judgment patterns. System performance was evaluated using the Mean Absolute Error (MAE) metric, which measures the average deviation between the model output and expert reference values. The results show that the Mamdani fuzzy model provides highly accurate and consistent classifications, indicated by a MAE value of 0.027 (2.7%). The error values for each laptop sample ranged from 0.02 to 0.04, demonstrating the model’s stability and effectiveness across various specification levels. These findings confirm that Mamdani fuzzy logic is suitable for laptop quality classification and can serve as a foundation for the development of intelligent recommendation systems for consumer electronics.